Z problematyki opisu frazeologii publicystycznej - Kosek, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article analyses the sources of phraseological units occurring in the media and in journalistic texts of contemporary Polish language. The first part of the article contains a few remarks on two types of new noun phrases, e.g. Europa dwu prędkości (two-/multi-speed Europe), mowa nienawiści (hate speech), dane wrażliwe (sensitive data). The second part indicates the main problems related to the linguistic description of phraseology in journalism: the phraseologism – term relation and the difficulties in identifying the sources of phraseological units (the type of loanword).